2017
DOI: 10.3329/ajmbr.v2i4.30990
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic analysis of heavy metal in frozen shrimp from different seafood processing plants of Chittagong, Bangladesh

Abstract: This study is carried out to determine the level of three common heavy metals i.e. mercury (Hg), lead (Pb) and cadmium (Cd) from different branded frozen shrimp samples from different processing plants in Chittagong Metropolitan Area, Bangladesh. The level of heavy metals is investigated by using Atomic Absorption Spectrophotometer (AAS) in twenty different frozen shrimp samples from four different processing plants. The range of mean level of concentration (mg/kg) of mercury (Hg), lead (Pb) and cadmium (Cd) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In Bangladesh, Cd is used in metal plating, plastics, pigments and batteries. Previous studies have found that different types of toys contain a considerable amount of Cd, posing a significant health risk to children 13,41. Cadmium is carcinogenic when inhaled, but there is no evidence that ingestion through drinking water poses a cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…In Bangladesh, Cd is used in metal plating, plastics, pigments and batteries. Previous studies have found that different types of toys contain a considerable amount of Cd, posing a significant health risk to children 13,41. Cadmium is carcinogenic when inhaled, but there is no evidence that ingestion through drinking water poses a cancer risk.…”
Section: Discussionmentioning
confidence: 99%